1955
DOI: 10.1021/ed032p606
|View full text |Cite
|
Sign up to set email alerts
|

Aromatic substitution by free radicals

Abstract: This article summarizes recent investigations upon orientation and reaction rates with respect to homolytic substitution.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 17 publications
0
3
0
Order By: Relevance
“…The situation changes in the presence of a nucleophilic molecule, like p ‐cymene or toluene. Compounds possessing an aromatic ring may undergo free radical aromatic substitution, which finally leads to the fast termination of the radical chain reaction. For p ‐cymene, it was shown that the substitution takes place at the position ortho to the methyl group.…”
Section: Resultsmentioning
confidence: 99%
“…The situation changes in the presence of a nucleophilic molecule, like p ‐cymene or toluene. Compounds possessing an aromatic ring may undergo free radical aromatic substitution, which finally leads to the fast termination of the radical chain reaction. For p ‐cymene, it was shown that the substitution takes place at the position ortho to the methyl group.…”
Section: Resultsmentioning
confidence: 99%
“…Conventionally, Fenton's reagent417, 418 has been in use as a source of hydroxyl radical, that can be used for organic synthesis as well as for degradation of organic pollutants. This reagent produces hydroxyl radical from hydrogen peroxide in the presence of iron, and is widely used for hydroxylation of benzene and its derivatives to phenol and phenolic compounds 419. The reactions can be summarized as: …”
Section: Applications Of Photocatalysismentioning
confidence: 99%
“…Therefore, the use of S2O8 2in contaminant treatment applications does not rely on the direct reaction between S2O8 2and contaminants but on the ability of S2O8 2to produce SO4 •and • OH, the process known as S2O8 2activation. The activation of S2O8 2takes place via the following reactions: (Nelson, 1955), reactions with SO4 •proceed mainly via the latter mechanism (Buxton et al, 1988). The byproducts produced from these reactions can be further oxidized by SO4 •and • OH to generate lower molecular-weight compounds that are often less toxic and more bioavailable.…”
Section: Persulfatementioning
confidence: 99%